Adsorption of phosphates using transition metals-modified bentonite clay. Issue 15 (13th October 2019) - Mdlalose, Lindani; Balogun, Mohammed; Setshedi, Katlego; Chimuka, Luke; Chetty, Avashnee
ABSTRACT: Phosphorus is a micronutrient but when it exists in abundance, it can have detrimental environmental impact. Bentonite (Bent) modified with Fe, Co and Ni salts were synthesized and evaluated for adsorption of phosphate ions from water. Results indicated that metal-modified bentonite have lower crystallinity compared to the native bentonite. Batch adsorption experiments showed maximum adsorption capacities of 20.88, 46.95, 29.07 and 6.57 mg/g for Fe-Bent, Co-Bent, Ni-Bent and Bent, respectively. The pseudo-second-order kinetic model provided a better fit for all adsorbents. The competition effect of coexisting anions were not significant for Fe and Ni modified bentonite.